Hubungan Sumber Air Bersih, Kepadatan Hunian, dan Daerah Tempat Tinggal dengan Kejadian Diare pada Balita di Indonesia - Zulfa Taqiyyah Ramadhani; Lailatul Muniroh; Chrysoprase Thasya Abihail (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Diarrhea is an endemic disease in Indonesia, and is often associated with high mortality rates, especially among infants and children. Diarrhea is the second leading cause of death among toddlers worldwide and directly contributes to malnutrition in toddlers. According to the Indonesian Health Profile in 2021, the mortality rate of toddlers due to diarrhea in Indonesia was recorded 10.3%. Poor sanitation is one of the determinants of diarrhea incidence in toddlers. Access to clean water supply and accupancy density are important aspects of household sanitation, while the geographical location, whether rural or urban, can also influence the environmental sanitation conditions. The objective of this study was to investigate the relationship between clean water supply, occupancy density, and geographical location with the incidence of diarrhea among toddlers in Indonesia. This study used secondary data from theÂ  Indonesian Demographic and Health Survey (IDHS) in 2017. Data were analyzed using the Pearson Chi-square statistical test with a significance level of Î± = 0.05. The results showed a significant relationship between clean water supply (p=0.014) and geographical location (p=0.001) with the incidence of diarrhea among toddlers. However, there was no significant relationship between occupancy density and the incidence of diarrhea among toddlers (p=0.199). In conclusion, inadequate sources of clean water and living in rural areas contribute to the incidence of diarrhea in toddlers. The government is strongly recommended to improve the quality of clean water sources and increase public knowledge regarding drinking water treatment to prevent diarrhea in toddlers, especially in rural areas.